The Outlandish Companion : Volume One : in which much is revealed regarding Outlander, Dragonfly in amber, Voyager, and Drums of autumn (and their author), including detailed synopses, commentary, controversy, glossaries, bibliographies and genealogies, TV shows, and other useful information - Gabaldon, Diana; Porter, Davina; Lyons, Susan, 1957-; Recorded Books, LLC. (Prince Frederick, MD : Recorded Books, 2015)
A guide to the Outlander series, time-travel romances featuring Claire Beauchamp Randall, a Red Cross nurse. Included are synopses of novels, biographies, family trees and pronunciation help.
Title from container.
Compact disc.
In container (17 cm.).
Narrated by the author, with Davina Porter and Susan Lyons.
Keywords: Gabaldon, Diana -- Authorship; Gabaldon, Diana -- Books and reading; Randall, Claire (Fictitious character); Fraser, Jamie (Fictitious character); Time travel in literature; Scotland -- In literature; Audiobooks; Romance fiction; Historical fiction; Fantasy fiction